Arabic Learning Challenges from the Perspective of Students in A Case Study Pilot School SMP Plus Pesantren Ainul Falah, Sekampung, East Lampung - Islakhul Munawaroh; Umar Najih Zein; Moh. Zulkifli Paputungan (Faculty of Education and Teacher Training, 2024)
Arabic is a compulsory subject at SMP Plus Ainul Falah Islamic Boarding School, Sumbergede, Sekampung, East Lampung, emphasizing foreign language skills as a key focus. However, teaching and learning Arabic face numerous challenges. Educators encounter obstacles due to limited experience, resource constraints, and high academic expectations. Students, often learning Arabic for the first time and coming from diverse backgrounds, face difficulties with grammar, language anxiety, and motivation. This qualitative descriptive research, conducted through a case study approach, explores these challenges to present an objective picture of the situation. Data were gathered from students at the boarding school. Findings highlight that grammatical differences pose significant learning hurdles, while language anxiety makes students hesitant to participate due to fear of mistakes or peer judgment. Additionally, low student motivation hampers learning progress. Addressing these challenges is crucial for enhancing Arabic learning outcomes at the school.